Preliminary Efficacy of a Multi-Behavioral Zoom-Based Peer Health Coaching Intervention in Young Adults: A Stepped Wedge Randomized Controlled Trial - Bilic, Anna; Burns, Ryan D; Bai, Yang; Brusseau, Timothy A; Lucero, Julie E; King Jensen, Jessica L (Cyberpsychology, behavior and social networking, 2023)
The purpose of this study was to test the preliminary efficacy of a Zoom-based peer coaching intervention on health and risk behaviors in young adults. A convenience sample of young adults was recruited from one U.S. university ( = 89; 73.0 percent female). Participants were randomized to one of two coaching session sequences within the framework of a stepped wedge randomized controlled trial. One experimental sequence received a control condition and a single coaching session, and the second sequence received two sessions. The intervention was a 1-hour program delivered by peer health coaches in a one-on-one setting on Zoom. The program consisted of a behavior image screen, a consultation, and goal planning. Behavioral assessments were completed after each condition. Mixed-effects models were employed to test for behavior differences after coaching sessions compared with the control condition (no coaching session) adjusting for baseline scores. Participants reported significantly higher levels of vigorous physical activity ( = 750 metabolic equivalent of task minutes, < 0.001), a lower frequency of e-cigarette use ( = -2.1 days; < 0.001), and a lower risk of e-cigarette susceptibility after two sessions (relative risk = 0.04, = 0.05), and higher odds of using stress reduction techniques after one session (odds ratio = 1.4, = 0.04). A nonsignificant trend was observed for longer weekday sleep ( = 0.4 h/night, = 0.11) after two coaching sessions. The Zoom-based peer health coaching intervention may be an efficient way to improve vigorous physical activity, lower e-cigarette use and susceptibility, and facilitate the use of stress reduction techniques in young adults. The results observed from this preliminary study warrants further investigation using powered effectiveness trials.